Inflammation and cardiovascular disease: are marine phospholipids the answer?. Issue 4 (9th April 2020) - Lordan, Ronan; Redfern, Shane; Tsoupras, Alexandros; Zabetakis, Ioannis
Abstract : This review presents the latest research on the cardioprotective effects of n-3 fatty acids (FA) and n-3 FA bound to polar lipids (PL). Overall, n-3 PL may have enhanced bioavailability and potentially bioactivity versus free FA and ester forms of n-3 FA. Abstract : Since the discovery that Greenlandic Innuits had a lower risk of developing cardiovascular diseases (CVD) due to their diet of fish and as a consequence high polyunsaturated fatty acids (PUFA) intake, scientific interest in the therapeutic value of n-3 PUFA such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) has grown. It is well-accepted that fish consumption is associated with the prevention of inflammation and CVD. As a result, fish oil supplements and nutraceuticals are widely consumed. Conversely, recent meta-analyses have cast doubt over the benefits n-3 PUFA due to heterogenous outcomes of numerous randomized controlled trials. However, the majority of clinical studies conducted have used n-3 PUFA supplements in their neutral forms as free fatty acids or bound to triacylglycerides (TAG) or ethyl esters. Current research indicates that n-3 PUFA bound to polar lipids (PL) such as phospholipids seem to exert differential bioavailability and biological effects upon consumption in contrast to neutral forms of n-3 PUFA. In this review, we discuss the promising health benefits of marine PL rich in n-3 PUFA that seem to go beyond those of neutral n-3 PUFA. However, further intensive research is required to discern the full extent of the biological activities of marine n-3 PL and their potential use in functional foods and nutraceuticals.